The contribution of Imam Shafi’I Hanafi, Maliki and Hambali to the field of religious sciences with particular reference to Islamic law - Ashimi, Tijani Ahmad (2020)
The contribution of Muslim scholars to the field of various knowledge is remarkable. Down the history, early Muslim scholars have contributed immensely to the field of Natural science, Social sciences, Human sciences and religious sciences ; perhaps, that is due to the intellectual freedom enjoyed by scholars which motivates them to think critically and creatively as well as their ability to transform the ideals of the Qur’an to daily conduct such as hard work, Perseverance, sincerity honesty and patience in seeking knowledge for the sake of knowledge. Based on this fact, this article aims to explore some achievements accomplished by some gigantic Muslim scholars ( such as Imam Shaf’i, Imam Hanafi, Imam Malik and Imam Ahmad bin Hanbal) to the field of religious sciences with particular reference to dimension of Islamic Law. Yet, to achieve the objective of this article, historical approach will be applied, that is by conducting historical study of their roots and personalities, followed by their Unique works and intellectual achievement. Lastly, the article will provide a brief conclusion and the lessons that can be learnt from the accomplishment of these genius Muslim Scholars.